2022 International Conference on Electrical, Computer, Communications and Mechatronics Engineering (ICECCME) 2022
DOI: 10.1109/iceccme55909.2022.9988381
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Cognitive Radio MIMO UAVs in Cellular Networks for 5G and Beyond

Abstract: In this paper, we study the performance of deploying multiple unlicensed unmanned aerial vehicles (UAVs) to share the spectrum and the base station of an established primary network in Multiple-Input-Multiple-Output (MIMO) communications. We present a novel power allocation scheme based on a combination of underlay cognitive radio with channel precoding and decoding to maximize the UAVs sum-rate. In the proposed scheme, we jointly use space alignment and successive interference cancellation techniques to minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It is known that capacity expression in MIMO systems is directly related to SNR. Therefore, the sub-optimization problem (15) for deriving F RF,1 can be approximately written as max…”
Section: Source Analog Precoder and Relay Rf Combinermentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that capacity expression in MIMO systems is directly related to SNR. Therefore, the sub-optimization problem (15) for deriving F RF,1 can be approximately written as max…”
Section: Source Analog Precoder and Relay Rf Combinermentioning
confidence: 99%
“…Just as minimizing the impact of interference on PUs caused by the SUs is important, it is also desirable to minimize the effect of interference on the SU due to the PU in CR communication. This task can be achieved by regulating the power transmission at the respective unit [ 15 , 16 , 17 ]. To maximize spectrum utilization in B5G wireless networks, it seems crucial to combine the dynamic spectrum allocation strategy with mm-wave transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this research is to assist in warehouse operational management by developing a Warehouse Management System (WMS) using the Extreme Programming method and implementing a temperature and humidity monitoring system based on the Internet of Things (IoT) integrated into the WMS. This monitoring system is built to assist warehouse's staff to monitoring warehouse temperature and humidity in real-time through the WMS, which can be accessed anytime and anywhere [17], [18], [19]. Temperature and humidity are important factors that can affect the quality of items, The method used to test the WMS is BlackBox Testing by executing system functions, and the results showed that the system successfully received responses for every request sent.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is also required to minimize the impact of interference on the SU caused by the PU in CR mode. This target can be achieved by regulating the transmit power of the SU [7]. From this perspective, it seems crucial to combine the dynamic spectrum allocation framework proposed by cognitive radio networks (CRN) with mm-wave communication to maximize spectrum utilization in B5G wireless cellular systems [8].…”
Section: Introductionmentioning
confidence: 99%